Submaximal laboratory anaerobic test to determine rhythmic gymnasts' fitness level - Gateva, M. (Journal of Applied Sports Sciences, 2019)
SUBMAXIMAL LABORATORY ANAEROBIC TEST TO DETERMINE RHYTHMIC GYMNASTS` FITNESS LEVEL Maria GatevaNational Sports Academy "Vassil Levski", Sofia, BulgariaABSTRACTIn sports such as gymnastics it is difficult to monitor the fitness and endurance level of the athletes. In rhythmic gymnastics it is proven that the competitive program is in anaerobic re-gime of work. Some authors state that there is no contribution by the aerobic energy system in gymnastics. Very few attempts have been undertaken to create specific anaerobic tests in the different gymnastics disciplines. That`s why the aim of this study was to create a laboratory test to measure the fitness level (specific endurance) of the rhythmic gymnasts competing at national and international level. Twelve high level gymnasts aged 15.7 (±2.1) were involved in this study. Two tests were performed in the laboratory - VO2max and submaximal 2-min test (author`s test) and one field test - competitive routine was carried out. Two min min submaximal treadmill test with constant load (95% of the maximal test)requires a 2-min run on a treadmill with a constant speed of 8,4 km/h and individually set up incline of 95% of the maximum for each athlete. The incline is fixed on the basis of: reached HR and incline during the maximal test; extrapolation of the incline as 100% from the theoretical maximal pulse and calculation of the 95% of the incline for each gymnast. Rhythmic gymnastics routine clearly showed better results in the competitive period and is an indicator for tapering into peak performance. We received some contradictory information as regards the laboratory results. Heart rate during the whole load on the treadmill test was lower (significantly proven). This means that in the next stage of the investigation, the experi-ment needs to be done with the same duration, but we should increase the load to 100%.